Fruit tree based alternate land use system for degraded rainfed lands - Kadam, D M; Bihari, Bankey; Bishnoi, Rajesh; Srimali, S S; Roy, Trisha; Malik, Anil (Indian Farming, 2022)
Adoption of fruit tree based cropping system in conjunction with site specific soil and water conservation measures can keep the production system sustainableand successfully ameliorate land facing degraded challenges in North West Himalayan Region (NWHR).Fruit tree species such as mango, guava, jackfruit, pomegranate, kagzi lime, bael and pomegranate has remarkable potential to augment farmers’ income and supports optimum utilization of land and natural resources. In addition, it can ensure short and longterm ecological, economical, livelihood and nutritional security of the farmers in terms of fruit, fuel, fodder and other ecosystem services. However, considering the stretched juvenile phase of fruit trees, long-termmonitoring is required for concrete recommendation. The capacity building and active participation were the most crucial aspects of the project. The outcomes wouldbe helpful for developing appropriate strategies and action plans for the management of natural resources and rehabilitation of wastelands through sustainable manner in lower NWHR.